ROLE OF INFORMATION TECHNOLOGIES IN THE PREVENTION AND CONTROL OF INFECTIOUS DISEASES (Modern education and development, 2025)
The application of information technologies (IT) in healthcare has transformed how infectious diseases are monitored, diagnosed, and controlled. This article discusses the role of IT in disease prevention and management, emphasizing tools such as telemedicine, big data analytics, and artificial intelligence. These technologies enhance global health systems' responsiveness, improving patient outcomes and public health strategies.